PERANCANGAN UI/UX DASHBOARD REPORTING PADA PORTAL HALAL.GO.ID MENGGUNAKAN METODE DESIGN THINKING - Anugradia, Nabila; Arsa, Daniel; Khaira, Ulfa (UIN Ar-Raniry, 2024)
The research aims to design a UI/UX dashboard reporting system for the Halal.go.id Portal using the design thinking method. This method involves research stages: Empathize, Define, Ideate, Prototype, and Test. The research employs qualitative methods with observation, interview, and heuristic evaluation techniques. The results indicate that the designed reporting dashboard achieved a score of 358 and a percentage of 89.50% based on 10 heuristic evaluation instruments, falling under the